2010
DOI: 10.1038/jhh.2010.72
|View full text |Cite|
|
Sign up to set email alerts
|

Insulin resistance in young, lean male subjects with essential hypertension

Abstract: Impaired insulin action, frequently found in essential hypertension (HT), is modified by other factors, such as higher age, accumulation of body fat, dyslipidaemia, impaired glucose metabolism and endothelial dysfunction. In addition, antihypertensive and insulin-sensitizing medication itself may significantly affect cardiovascular and metabolic milieu. The aim of this study was to assess insulin sensitivity, acute insulin response, lipidaemic status and the adipokines' concentrations with regard to abdominal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 61 publications
(62 reference statements)
1
12
0
Order By: Relevance
“…[7][8][9][10] The mean value of HOMA-IR was significantly higher in adult male with essential hypertension when compared with that of controls. Systolic blood pressure and diastolic blood pressure show positive correlation with HOMA-IR but was significant only with systolic blood pressure.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…[7][8][9][10] The mean value of HOMA-IR was significantly higher in adult male with essential hypertension when compared with that of controls. Systolic blood pressure and diastolic blood pressure show positive correlation with HOMA-IR but was significant only with systolic blood pressure.…”
Section: Discussionmentioning
confidence: 96%
“…It has been suggested that sympathetic over activity may lead to structural changes in the microvasculature, which ultimately increases blood pressure and decreases peripheral glucose uptake. [7][8][9][10] Again, essential hypertensive subjects have significant defect in activating the insulin receptor. There is decreased insulin action on insulin receptor (IR) which reduces the activation of receptor tyrosine kinase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have identified an association between hyperinsulinemia (elevated fasting and postprandial insulin levels) and hypertension. [7][8][9] In contrast some investigators observed no significant difference between the healthy subjects and essential hypertensive patients in regard to fasting serum insulin level. [10][11] So, the precise nature of the relationship between fasting serum insulin level and essential hypertension remains still obscure.…”
Section: Introductionmentioning
confidence: 83%
“…Male rats with hypertension, also known as SHR, constitute an appropriate model for experimental studies regarding the effects of hypertension on different organs. As previously mentioned, apart from SHR rats, SHRsp and ZDF rat models are used (Buchanan et al, 1992;Penesova et al, 2011;Satoh et al, 2014). Satoh and coworkers (2014) had conducted research including the assessment of hypertension-induced morphological changes in the pancreatic islets of SHRsp.…”
Section: Essential Hypertensionmentioning
confidence: 99%